Bonjour,
f(x) = ax³ + bx² + cx + d
f'(x) = 3ax² + 2bx + c
⇔ a*0³ + b*0² + c*0 + d = 0 ⇔ d = 0
⇔ y = cx
(1) ⇒ c = -0,6
⇒ f(x) = ax³ + bx² - 0,6x et f'(x) = 3ax² + 2bx - 0,6
2)
⇔ a*6³ + b*6² - 0,6*6 = 3,6
⇔ 216a + 36b - 3,6 = 3,6
⇔ 216a + 36b = 7,2
⇔ 72a + 12b = 2,4 (en divisant par 3)
⇔ 3a*6² + 2b*6 -0,6 = 0
⇔ 108a + 12b = 0,6
3)
72a + 12b = 2,4 (1)
108a + 12b = 0,6 (2)
(2) - (1) ⇒ 108a - 72a = 0,6 - 2,4 ⇔ 36a = -1,8 ⇔ a = -1,8/36 = -0,05
(1) ⇒ 12b = 2,4 - 72a ⇔ 12b = 2,4 - 72*(-0,05)
⇔ 12b = 2,4 + 3,6 ⇔ 12b = 6 ⇔ b = 6/12 = 0,5
⇒ f(x) = -0,05x³ + 0,5x² - 0,6x